Tolerability, safety, and pharmacokinetics of a single intravenous administration of a novel recombinant humanized anti-interleukin-6 receptor monoclonal antibody in healthy Chinese volunteers - Jiang, Xin; Lin, Pingping; Sun, Feifei; Xu, Yi; Tao, Ye; Shi, Ping; Liu, Yanping; Li, Xin; Liu, Shuqin; Gao, Xiaomeng; Wang, Chenjing; Cao, Yu (Frontiers in Pharmacology, 2024)
Aim: VDJ001 is a novel recombinant humanized monoclonal antibody against the anti-interleukin-6 receptor. As an analog of tocilizumab, it exhibited improved affinity and in vitro activity. Based on preclinical studies, a first-in-human clinical study was conducted to evaluate the safety, tolerability, and pharmacokinetics of VDJ001. Methods: This is a single-center, randomized, double-blinded, placebo-controlled phase I dose-escalation study conducted in healthy Chinese volunteers. Four cohorts were designed with dosages ranging from 1 to 8 mg/kg. There were equal numbers of female and male volunteers in each cohort. Enrolled subjects randomly received a single intravenous administration of VDJ001 or placebo (VDJ001: placebo = 4:1 in both female and male volunteers). Three sentinel volunteers in the 1 mg/kg cohort were first administered, and the treatment of the other seven volunteers was carried out after a safety assessment on D15. The following cohort was conducted only when the safety profile was evaluated as acceptable on D29 of the previous cohort. Samples for pharmacokinetics (PK), pharmacodynamics (PD), and immunogenicity were collected at specified time points and analyzed through validated methods. Adverse events and the results of the examination and laboratory were analyzed to assess the safety profile. Results: All cohorts were carried out according to the protocol. With the escalation of dosage, Cmax increased linearly, and AUC0-t and AUC0-∞ increased in a non-linear manner, while clearance decreased and t1/2 prolonged. Six volunteers who received VDJ001 tested ADA-positive, among whom one participant tested Nab-positive on D57. One volunteer in the placebo group tested ADA-positive but Nab-negative. CRP concentrations were not found to be correlated with the dosage. Both IL-6 and sIL-6R concentrations increased after the administration of VDJ001. All adverse events were mild to moderate in severity. No serious adverse events were reported in this study. No unexpected or clinically significant safety issues were found. Conclusion: The safety and tolerability of VDJ001 are acceptable with a single intravenous dosage of 1∼8 mg/kg. Further clinical trials are warranted.